The differential effects of sleep deprivation on pain perception in individuals with or without chronic pain: A systematic review and meta-analysis. (December 2022) - Chang, Jeremy R.; Fu, Siu-Ngor; Li, Xun; Li, Shirley X.; Wang, Xiaoyue; Zhou, Zhixing; Pinto, Sabina M.; Samartzis, Dino; Karppinen, Jaro; Wong, Arnold YL.
Abstract: Many experimental sleep deprivation (SD) studies were conducted to clarify the causal relationship between sleep and pain. This systematic review and meta-analysis aimed to update the evidence regarding the effects of different experimental SD paradigms on various pain outcomes. Five databases were searched from their inception to June 2022. Separate random-effects models were used to estimate the pooled effect sizes (ES) of different experimental SD paradigms on various pain outcomes. Thirty-one studies involving 699 healthy individuals and 47 individuals with chronic pain were included. For healthy individuals, limited evidence substantiated that total SD significantly reduced pain threshold and tolerance (ES 0.74–0.95), while moderate evidence supported that partial SD significantly increased spontaneous pain intensity (ES 0.30). Very limited to moderate evidence showed that sleep fragmentation significantly increased peripheral and central sensitization in healthy individuals (ES 0.42–0.79). Further, there was very limited evidence that total or partial SD significantly aggravated spontaneous pain intensity in people with chronic pain. Our results accentuated that different SD paradigms differentially increased subjective pain intensity and worsened peripheral/central pain sensitization in healthy individuals, whereas the corresponding findings in people with chronic pain remain uncertain. Further rigorous studies are warranted to quantify their relationships in clinical populations.